2006
DOI: 10.3758/bf03193875
|View full text |Cite
|
Sign up to set email alerts
|

Vision-for-action: The effects of object property discrimination and action state on affordance compatibility effects

Abstract: The role of object affordances and center of gravity in eye movements toward isolated daily-life objects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
192
7
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(220 citation statements)
references
References 18 publications
19
192
7
2
Order By: Relevance
“…It has been shown that attention is a necessary condition for low-level sensory-motor mechanisms to be activated. For instance, in the domain of affordance perception, Tipper et al (S. Tipper et al 2006;S. P. Tipper 2010) instructed participants to report the colour of door-handles presented on a computer screen, thus focusing their attention on a non-action relevant object feature.…”
Section: Figure 3 Near Here Discussionmentioning
confidence: 99%
“…It has been shown that attention is a necessary condition for low-level sensory-motor mechanisms to be activated. For instance, in the domain of affordance perception, Tipper et al (S. Tipper et al 2006;S. P. Tipper 2010) instructed participants to report the colour of door-handles presented on a computer screen, thus focusing their attention on a non-action relevant object feature.…”
Section: Figure 3 Near Here Discussionmentioning
confidence: 99%
“…Also in conflict with the notion of strictly automatic activation of affordances, attention to the semantic properties (e.g., goal-directed use) of the graspable objects was shown to reliably modulate the affordance effect. When the experimental task is relevant to the grasp-related potential of the perceived object, the resulting affordance effect is stronger (Creem and Proffitt, 2001;Shuch et al, 2010;Tipper, Paul, and Hayes, 2006).…”
Section: Visual and Linguistic Cues To Manual Grasp Affordancesmentioning
confidence: 99%
“…However, there is an abundance of evidence that perceptual stimuli and actions can be strongly associated (Fagioli, Ferlazzo, & Hommel, 2007;Fagioli, Hommel, & Schubotz, 2007;Humphreys et al, 2010;von Cramon 2002, 2003;Tipper 2010;Tipper, Paul, & Hayes, 2006;Tucker and Ellis 1998), and can be integrated to form a single event or episode (Barsalou 2009;Hommel 2004Hommel , 2005Hommel et al, 2001;Logan 1988). According to Logan and Etherton (1994), each episode represents a specific combination of goals, stimuli, interpretations, and responses that occur together on a specific occasion.…”
Section: Discussionmentioning
confidence: 99%
“…It is argued that motor activation is induced by action words, affordances of perceptual objects, and other perceptual events because motor activation is intrinsically linked to the processing of semantics and affordances (e.g., Fagioli, Ferlazzo, & Hommel, 2007;Fagioli, Hommel, & Schubotz, 2007;von Cramon 2002, 2003;Tipper et al, 2006;Tucker and Ellis 1998). In other words, motor activation is part of the meaning or concept, regardless of whether the meaning or concept is represented by a word(s), object(s), or actions of another individual (e.g., Pulvermüller 2005;Rueschemeyer, Lindemann, Van Elk, & Bekkering, 2009), which is consistent with modal theories of memory (e.g., Barsalou 2009;Barsalou et al, 2003).…”
Section: Discussionmentioning
confidence: 99%